Der Sonderfonds für Kulturveranstaltungen – ein Versicherungsinstrument - Alexander Mislin (Wirtschaftsdienst, 2022)
Der Sonderfonds des Bundes für Kulturveranstaltungen ist das zentrale Instrument zur Unterstützung der Kultur- und Veranstaltungsbranche und dabei eines von mehreren Maßnahmen, die von Bund und Ländern zur Bewältigung der Coronapandemie aufgelegt wurden. Der Sonderfonds ist ein versicherungsartiges Instrument, das Planungssicherheit im Vorfeld und bei der Durchführung von Veranstaltungen geben soll. Der Sonderfonds ist mit bis zu 2,5 Mrd. Euro ausgestattet und startete am 1. Juli 2021. – – The federal special fund for cultural events is the central support instrument for the culture and events industry and is one of several measures that have been put in place by the federal and state governments to deal with the coronavirus pandemic. The special fund is an insurance-like instrument that is intended to provide planning security in the run-up to and during events. It is endowed with 2.5 billion euros and started on 1 July, 2021. The low outfl ow of funds in relation to the sum insured demonstrates the fund's importance as insurance for the culture and event industry during the pandemic.
Keywords: H12; I38; Z10; 330; Kultursektor; Veranstaltungswirtschaft; Coronavirus; Subvention; Deutschland